Assessing the Security and Privacy of Baby Monitor Apps - Lukas Schmidt; Henry Hosseini; Thomas Hupperich (Journal of Cybersecurity and Privacy, 2023)
Emerging technologies in video monitoring solutions seriously threaten personal privacy, as current technologies hold the potential for total surveillance. These concerns apply in particular to baby monitor solutions incorporating mobile applications due to the potential privacy impact of combining sensitive video recordings with access to the vast amount of private data on a cell phone. Therefore, this study extends the state of privacy research by assessing the security and privacy of popular baby monitor apps. We analyze network security measures that aim to protect baby monitoring streams, evaluate the corresponding privacy policies, and identify privacy leaks by performing network traffic analysis. Our results point to several problems that may compromise user privacy. We conclude that our methods can support the evaluation of the security and privacy of video surveillance solutions and discuss how to improve the protection of user data.